Priming effect of bivalent and quadrivalent vaccine for HPV 31/33/45/52: an exploratory analysis from two clinical trials - Chantal Sauvageau; Gitika Panicker; Elizabeth R. Unger; Gaston De Serres; John Schiller; Manale Ouakki; Vladimir Gilca (Taylor & Francis Group, 2020)
The main objective of this post hoc analysis is to compare the magnitude of the immune response to HPV31/33/45/52 and 58 after a dose of 9vHPV vaccine given to naïve (previously unvaccinated) subjects and subjects previously vaccinated with a dose of 2vHPV or 4vHPV vaccine. Results from two clinical trials conducted in the same region, in comparable populations and by the same research team were included in this analysis. In study A, a dose of 9vHPV was administered 6 months after a single dose of 2vHPV as well as to naïve subjects. In study B, a dose of 9vHPV was administered 36-96 months (mean 65 months) after a single dose of 4vHPV. Blood samples were collected just before and one month post-9vHPV vaccine administration. For both studies, antibody responses were measured using the same 9-plex virus-like particle based IgG ELISA (M9ELISA). One month after 9vHPV dose administration, all subjects were seropositive to HPV 31/33/45/52 and 58. Subjects who had previously received 2vHPV or 4vHPV had significantly higher (1.8-8.0-fold) GMTs than naive subjects for HPV31/33/45/52 types but not for HPV58. GMTs to HPV31/33/45/52 and 58 were not significantly different between subjects who received a 2vHPV or 4vHPV dose prior to 9vHPV. The strong anamnestic response to one dose of 9vHPV given as late as 3-8 years after a single dose of 2vHPV or 4vHPV vaccine indicates these vaccines induced priming to types only included in the 9vHPV vaccine.